2016
DOI: 10.1088/1674-1056/25/2/026104
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure structural properties of tetramethylsilane

Abstract: High-pressure structural properties of tetramethylsilane are investigated by synchrotron powder x-ray diffraction at pressures up to 31.1 GPa and room temperature. A phase with the space group of Pnma is found to appear at 4.2 GPa. Upon compression, the compound transforms to two following phases: the phase with space groups of P21/c at 9.9 GPa and the phase with P2/m at 18.2 GPa successively via a transitional phase. The unique structural character of P21/c supports the phase stability of tetramethylsilane wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Fortunately, an exception was found in tetramethylsilane (Si­(CH 3 ) 4 ), which is also one of the Group IVa hydrides and yet shows no decomposion at pressures up to 142 GPa . Although it remains unknown whether Si­(CH 3 ) 4 could be metalized or not, our previous work by Raman spectroscopy revealed that new Raman modes, which appeared at around 100 GPa, underwent a dramatic softening and characterized Si­(CH 3 ) 4 as semimetallic state possibly as in the case of hydrogen at high pressures. , Even more interestingly, the CH 3 groups within such meterials were proved to be a motivating factor both for maintaining stability under compression and for the softening behaviors of those modes. , Moreover, the CH 3 group also shows various interesting behaviors at high pressures, including the restriction in the rotation of the CH 3 group in some compounds (such as CH 3 Hg M (M = Cl, Br, I) and (CH 3 ) 2 XM (X = Sn or Tl) , ) and the different rotational angles in cubic Si­(CH 3 ) 4 at 0.58 GPa etc. Additionally, the recent breakthrough in the discovery of superconductivity above recorded high 190 K in H–S compound indicates the possibility of high-temperature superconductivities in hydrogen-dominant hydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, an exception was found in tetramethylsilane (Si­(CH 3 ) 4 ), which is also one of the Group IVa hydrides and yet shows no decomposion at pressures up to 142 GPa . Although it remains unknown whether Si­(CH 3 ) 4 could be metalized or not, our previous work by Raman spectroscopy revealed that new Raman modes, which appeared at around 100 GPa, underwent a dramatic softening and characterized Si­(CH 3 ) 4 as semimetallic state possibly as in the case of hydrogen at high pressures. , Even more interestingly, the CH 3 groups within such meterials were proved to be a motivating factor both for maintaining stability under compression and for the softening behaviors of those modes. , Moreover, the CH 3 group also shows various interesting behaviors at high pressures, including the restriction in the rotation of the CH 3 group in some compounds (such as CH 3 Hg M (M = Cl, Br, I) and (CH 3 ) 2 XM (X = Sn or Tl) , ) and the different rotational angles in cubic Si­(CH 3 ) 4 at 0.58 GPa etc. Additionally, the recent breakthrough in the discovery of superconductivity above recorded high 190 K in H–S compound indicates the possibility of high-temperature superconductivities in hydrogen-dominant hydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid technological advancements in recent years allow strong squeezing to be generated in a number of nonlinear processes and quantum systems, e.g., parametric oscillators, [9][10][11][12] second harmonic generation, [13] atom-cavity couplings, [14][15][16] semiconductor microcavities, [17][18][19] optomechanical, [20][21][22] and nonlinear directional couplers (NLDC). [23][24][25][26] Systems having inherent fast nonlinear response, such as Kerr NLDC, however, possess the potential in generating strong squeezed light, especially when placed inside a cavity to resonantly amplify the nonlinearity.…”
Section: Introductionmentioning
confidence: 99%